When Employees Experience Low Levels of Job Autonomy, Fair Procedures Buffer Unfair Outcomes - Versteegt, Lisanne; van Dijke, Marius; van Ruysseveldt, Joris; van den Bos, Kees (Frontiers in Psychology, 2022)
Organizations play a key role in maintaining employee well-being. Some research suggests that one way to protect employee well-being is to treat them fairly (procedural justice), especially when fair job outcomes (distributive justice) cannot be ensured. Yet, previous studies have not consistently found this interaction effect between distributive and procedural justice. This study investigates job autonomy as a boundary condition to the Distributive Justice × Procedural Justice effect on well-being outcomes. To test our hypothesized three-way interaction between distributive justice, procedural justice, and job autonomy, we collected cross-sectional data among Dutch employees in two studies. We used validated self-report measures of our core constructs to test our hypothesis on two employee well-being indicators: job satisfaction and emotional exhaustion. Results show a significant three-way interaction effect on both job satisfaction and emotional exhaustion in Study 1 (N = 411), and a significant three-way interaction effect on emotional exhaustion in Study 2 (N = 1117). Simple slopes analyses of the significant three-way interactions showed that distributive justice and procedural justice interact to predict well-being outcomes among employees with low job autonomy. Among employees with high job autonomy, distributive justice and procedural justice do not interact to predict well-being. The results contribute to the employee well-being literature by showing that job autonomy is a boundary condition to the Distributive Justice × Procedural Justice effect on well-being outcomes. We discuss other implications of our findings for the workplace and the ramifications for employees with low and high job autonomy.